2017
DOI: 10.1016/j.jvb.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Coping with newcomer “Hangover”: How socialization tactics affect declining job satisfaction during early employment

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 81 publications
0
22
0
2
Order By: Relevance
“…The honeymoon-hangover effect occurs where a job change engenders an uplift in satisfaction that subsequently decreases over time (Boswell, Boudreau, & Tichy, 2005). Satisfaction peaks are particularly high for those who learn more during socialization (Boswell, Shipp, Payne, & Culbertson, 2009), whilst institutionalized socialization tactics can reduce any decrease in satisfaction that occurs after this peak (Wang, Hom, & Allen, 2017).…”
Section: Organizational Socializationmentioning
confidence: 99%
“…The honeymoon-hangover effect occurs where a job change engenders an uplift in satisfaction that subsequently decreases over time (Boswell, Boudreau, & Tichy, 2005). Satisfaction peaks are particularly high for those who learn more during socialization (Boswell, Shipp, Payne, & Culbertson, 2009), whilst institutionalized socialization tactics can reduce any decrease in satisfaction that occurs after this peak (Wang, Hom, & Allen, 2017).…”
Section: Organizational Socializationmentioning
confidence: 99%
“…Socializacijos taktikos. Mokslininkų (van Maanen ir Schein, 1979;Miller ir Jablin, 1991;Cooper-Thomas ir Anderson, 2006;Wang et al, 2017; Kowtha, 2018 ir kt.) tyrimai rodo, kad darbuotojų pasitelkiamos socializacijos taktikos dažniausiai siejasi su informacijos siekiu ir santykių kūrimu.…”
Section: Naujų Darbuotojų Socializacija: Teoriniai Požiūriai Tyrimų unclassified
“…1. Naujų darbuotojų socializacijos metmenų (Taormina, 1994(Taormina, , 1997 ir kitų socializacijos rodiklių (Wang et al, 2017;Cooper-Thomas ir Anderson, 2006;Pollock et al, 2000 ir kt.) vertinimas tarpusavyje koreliuoja; 2.…”
Section: Naujų Darbuotojų Socializacija: Teoriniai Požiūriai Tyrimų unclassified
“…However, another important step for re-defining the psychological contract is when new agents start working in operational contexts (Institutes). Further, the two stages could be affected by the honeymoon-hangover pattern ( Boswell et al, 2009 ; Wang et al, 2017 ), due to the 7-month time span and to the direct knowledge of the operational context that newcomers had during the stage (just before time 2). Thus, it would be appropriate in future research to do a longitudinal study with a larger number of observation times, in order to monitor the development of a psychological contract in a broader time frame.…”
Section: Studymentioning
confidence: 99%
“…Overall, scholars have suggested that newcomers’ experiences in this stage will influence not only organizational outcomes (e.g., motivation or commitment), but also the further development of their psychological contract ( De Vos et al, 2003 ; Sutton and Griffin, 2004 ; Tomprou and Nikolaou, 2011 ; Wanberg, 2012 ). For instance, usually newcomers at first have idealized or poorly defined views of their employment relationship ( Lance et al, 2000 ) and there are different patterns that can occur in the period after that, such as the honeymoon-hangover pattern ( Boswell et al, 2009 ; Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%